Assessment of humoral and cellular immune responses to SARS CoV‐2 vaccination (BNT162b2) in immunocompromised renal allograft recipients. Issue 2 (3rd March 2022) - Zhang, Ruan; Shin, Bong‐Ha; Gadsden, Terry‐Ann M.; Petrosyan, Anna; Vo, Ashley; Ammerman, Noriko; Sethi, Supreet; Huang, Edmund; Peng, Alice; Najjar, Reiad; Atienza, Janet; Kim, Irene; et al.
Abstract: Background: Assessing the composition of immune responses to SARS‐CoV‐2 vaccines is critical for our understanding of protective immunity, especially for immune compromised patients. The Pfizer (BNT162b2) vaccination showed >90% efficacy in protecting individuals from infection. However, these studies did not examine responses in immunocompromised kidney transplant patients (KT). Subsequent reports in KT have shown severe deficiencies in Spike‐specific immunoglobin G (IgG) responses prompting booster vaccinations, but a broader understanding of T‐cell immunity to vaccinating is lacking. Methods: We examined SARS‐CoV‐2 Spike IgG and CD4+/CD8+ Spike‐specific T‐cell responses in 61 KT patients maintained on different immunosuppressive protocols (ISP) (Tac + mycophenolate mofetil + prednisone) versus (belatacept + MMF + prednisone) and compared to 41 healthy controls. We also examined cytomegalovirus‐cytotoxic T‐cell responses (CMV‐Tc) in both groups to assess T‐cell memory. Results: Our data confirmed poor Spike IgG responses in vaccinated KT patients with both ISP (21% demonstrating Spike IgG 1M post‐second dose of BNT162b2 vs. 93% in controls). However, 35% of Spike IgG (‐) patients demonstrated CD4+ and/or CD8+ T‐cell responses. All but one CMV‐IgG+ patient demonstrated good CMV‐Tc responses. No differences in T‐cell immunity by ISP were seen. Conclusion: Immunocompromised KT recipients showed severe defects in humoral and T‐cell immune response after vaccination. No differences in immune responses to SARS‐CoV‐2 Spike peptides were observed in KT patients by ISP post‐vaccination. The detection of Spike‐specific T‐cell immunity in the absence of Spike IgG suggests that vaccination in immunocompromised KT patients may provide partial immunity, although not preventing infection, T‐cell immunity may limit its severity.